Payments for conservation of animal genetic resources in agriculture: One size fits all? - Juvančič, Luka; Slabe-Erker, Renata; Ogorevc, Marko; Drucker, Adam G.; Erjavec, Emil; Bojkovski, Danijela (MDPI, 2021)
Maintaining minimum population sizes for local livestock breeds is a key goal in the conservation of animal genetic resources. As markets and livestock production systems have tended to favour a narrow base of high-output improved breeds, countries have had to use financial and other incentives to motivate breeders to keep local breeds. This paper explores the potential for more cost-effective alternatives to the most commonly used financial incentive, a fixed payment per animal or livestock unit. We compare the current fixed payment incentives for local breeds under the Slovenian Rural Development Programmme with those instead determined through a competitive tender approach. A stated preference survey was realised to determine the conditions under which breeders would be willing to participate in such an incentive system based on differentiated payments. Willingness to accept (WTA) payment for conservation was found to differ significantly from actual payment levels, being lower for the local sheep and goat breeds, and higher for the local pig breed. This suggests that implementation of differentiated payments would be more cost-effective; particularly when accompanied by measures to streamline administrative requirements, improve access to breeding stock and target support for local breed market valorisation (e.g., promotion of value chains based on designated quality schemes).